Cultural Studies and Symbolism of Tapis Cloth Motifs in the Culture of Lampung People - Majid, Abdul; Widya Dina (Enigma in Cultural, 2023)
The traditional textile art in Lampung, Indonesia, holds significant cultural significance and is imbued with intricate symbolism. The images found on Tapis cloth not only showcase aesthetic appeal but also encompass profound cultural teachings, spiritual values, and symbolism that profoundly influence the lives of the Lampung people. Tapis cloth patterns embody diverse cultural elements such as mythology, spiritual convictions, a symbiotic connection with the environment, ethnic heritage, equilibrium, safeguarding, and the pursuit of prosperity. Tapis fabric serves as a means of conveying ancient narratives, commemorating cultural legacies, and preserving unique cultural individuality.